Akumulasi Timah Hitam dalam Daging dan Tulang Ayam Kampung dan Ayam Negeri (LEAD ACCUMULATION IN MEAT AND BONES OF DOMESTIC AND BROILER CHICKEN) - ., Djohan; Tabbu, Charles Rangga (Jurnal Veteriner, 2016)
Lead is a heavy metal polluting the environment, and its accumulation in animal or human bodies canhave neurotoxic and nephrotoxic effects on animals and human. Lead-contaminated chicken meat can bethe source of lead to human. Lead exposure to human can be assessed by measuring its concentration andaccumulation in chicken body parts and analyzing chicken consumption patterns. This study was conductedto measure lead concentrations in chicken body parts and to estimate lead exposure caused by consumptionof chicken body parts (breast, legs, wings) and tissues (meat, skin, cartilage, spongy bones). Samples wereextracted by using aqua regia digestible method with a mixture of HCl: HNO3 (3:1; v/v) and leadconcentrations were measured by the Atomic Absorption Spectrophotometry (AAS) method. The leadconcentrations in chicken tissues varied from< 0.01 to 1.81?g.g-1dry weight.The average concentrations oflead in chicken tissues were lower than the recommended safety level of lead in chicken meat (1.0?g.g-1),except for the breast cartilage (1.03?g.g-1). The lowet accumulation level 2.6 ?g g-1 was found in domesticchicken wings while the highest of 32.9 ?g g-1 was found in broiler chicken breast (total of meat, skin,cartilage). Based on the data of lead accumulation in chicken tissues, a polynomial equation describing theprobability (P) to be exposed to certain amount of lead in chicken tissues (A, in ?g) was determined as P =-(1 x 10-3)A2 + (6,4 x 10-2)A.
Keywords: lead; accumulation; exposure